Inovatif Integratif Kebijakan Energi dan Ketahanan Pangan - Gaspar Pera (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
There are three main global challenges faced in all fields, namely complexity, change and increasing problems. A monodisciplinary approach with a single technology approach is no longer relevant to face these conditions. Innovation, integration and sustainability are the keys to face these three challenges, especially towards zero carbon emission energy that is operational. To produce bioethanol as a zero carbon emission energy source, the problem is that a large amount of thermal energy is required and a lot of "waste" is produced in the production process. It also requires the right raw materials that do not compete with food. All of these problems with conventional approaches have not been able to produce production costs (HPP) that compete with other renewable energy sources, let alone with fossil energy. The proposed innovation is an integrative innovation that will produce bioethanol as energy that is not only zero emission but negative emission with low HHP. This can be achieved through integrative synergy of biochar production with appropriate technology researched so far that produces large surplus energy and sorghum farming as raw material. The biochar product produced as a co-product is a multi-functional product of high economic value. If part of the biochar is utilized in agriculture, it not only increases the yield of therapeutic agriculture as a stable carbon sequestration in the soil. Sweet sorghum is an agricultural crop that has high adaptation to natural conditions with high seed and biomass production. Sorghum is ideal as a feedstock for ethanol and food production. Integrating the three with the right innovation will produce bioethanol with negative carbon emissions and co-products with low COGS. Sorghum juice is used as a first generation feedstock (FGR) and its bagasse as a second generation source (SGR). This integration involves the utilization of juice extraction by expeller technique and pretreatment of a combination of mechanical, steam explosion and organosolv methods that do not produce hazardous waste. The entire process is designed with the concept of maximum closed loop and minimum input. The system is open for various other integrations and developments in the future to support the concept of green economy.